Åker- och skogsmark: en prisjämförelse över tid - Rosén, Fredrik (2015)
In Sweden the market for forest land as well as arable land has had an intense growth since the middle of the 1990’s. The purpose of this study is to substantially look upon the trends regarding growth in prices for the types of land mentioned. Over and above this study also compare the growth in land prices with the growth in prices of products harvested. As a complement and explanation to the development the inquiry “Minienkäten”, published by the Ordnance Survey in Sweden, has also been looked upon. This inquiry is published twice a year and reflects the opinions from persons involved in the business (realtors, banks, forestry companies et cetera). Statistics from the Ordnance Survey in Sweden has been used as the primary source for land prices. Products harvested that has been used for comparison in the study are the net income for harvested wood and wheat prices. The source for harvested wood is the Swedish Forest Board and for wheat the Swedish Board of Agriculture as well as the French commodity exchange, MATIF. To be able to utilize the information handed by the Ordnance Survey in Sweden the initial part of the study is to look upon the structure of the Swedish property system. As a complement the system for wheat trade and the system for sorting out the net income of harvested wood in Sweden are also looked upon. The study covers the years 2001 to 2012 and compares 46 000 real estate purchases. The conclusion is that property formations are more intense than the jurisprudent purchases when it comes to growth in prices. The connection between land prices and prices for products harvested is getting weaker, land prices are constantly growing while prices for products harvested are more volatile. The main conclusion from the study is that there are more to a property purchase then the net income from products harvested!